AGE-RELATED FEATURES OF COMMON CAROTID ARTERIES IN PATIENTS WITH ARTERIAL HYPERTENSION, CHRONIC OBSTRUCTIVE PULMONARY DISEASE, AND THEIR COMBINATION - O. V. Milyutina; E. N. Chicherina (Российский кардиологический журнал)
The study was aimed at investigating endothelial function of common carotid arteries in patients with isolated arterial hypertension (AH), isolated chronic obstructive pulmonary disease (COPD), and their combination. The study included 67 patients with AH and COPD, as well as 45 patients with either AH or COPD (the comparison group), aged from 40 to 50 and from 51 to 60 years. Ultrasound assessment of common carotid artery (CCA) intima-media thickness (IMT) demonstrated significantly increased IMT in patients with a combination of AH and COPD, comparing to participants with isolated AH or COPD. In addition, CCA stenosis was observed in COPD patients and individuals with AH combined with COPD.